Hanging in, but only just: Part-time employment and in-work poverty throughout the crisis - Jeroen Horemans; Ive Marx; Brian Nolan (IZA Journal of European Labor Studies, 2016)
The crisis has deepened pre-existing concerns regarding low-wage and non-standard employment. Countries where unemployment increased most strongly during the crisis period also saw part-time employment increasing, particularly involuntary part-time work. With involuntary part-time workers, as a particular group of underemployed, facing especially high poverty rates, this was accompanied by an increase, on average, in the poverty risk associated with working part-time. However, this was not reflected in a marked increase in the overall in-work poverty rate because full-time work remains dominant and its poverty risk did not change markedly. The household context is of the essence when considering policy implications.
Keywords: I32; I38; J21; J22; J68; R28; 330; In-work poverty; Part-time employment; Involuntary part-time employment; Crisis Europe